Early Puberty Trend during the COVID-19 Pandemic in Singapore : A Retrospective Review in a Single Tertiary Centre - Leong, Annie; Vasanwala, Rashida Farhad (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objectives. We aimed to study the trend of referrals for precocious puberty during the COVID-19 pandemic compared to pre-COVID years, explore the differences in the demographic and clinical features, and evaluate the contributing factors. Methodology. The cases referred for assessment of PP from 2018-2021 to our endocrine centre were grouped into pre-COVID (2018-2019) and COVID (2020-2021) years. Cases fulfilling the diagnosis of PP included the onset of thelarche <8 years in females and 4mls testicular volume <9 years in males. The PP was further differentiated as Isolated Thelarche (IST) and Central Precocious Puberty (CPP). Early menarche was defined as menarche <10 years old. Results. There were more referrals for PP and more diagnosed as CPP during the COVID-19 pandemic, predominantly among females. There were more endocrine tests done and more cases received treatment. None of the abnormal magnetic resonance imaging (MRI) pituitary findings required surgical intervention. The body mass index (BMI) was found to be positively associated with the risk of getting CPP with a crude-odd ratio (COR) of 1.8, P <0.001, and early menarche (COR 2.1, P <0.001). Conclusion. We found a significant increase in the referrals of PP and diagnosis of CPP during the COVID-19 pandemic. Higher BMI was found to be associated with CPP and early menarche.